2021
DOI: 10.1177/14624745211041845
|View full text |Cite
|
Sign up to set email alerts
|

Carcerality and the legacies of settler colonial punishment in Nairobi

Abstract: From the beginning of its colonial settlement in Kenya, the British administration criminalized Kenyans. Even now, colonial modes of punishment, incarceration, closure, interrogation, curfew, confiscation, separation, displacement, and detention without trial are deeply embedded in the spatial and ideological arrangements of post-colonial Kenya. Initially assumed to herald a rupture from colonial modes of criminalization and punishment, the post-colonial period instead normalized them. Through ethnographic, sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…The injury and harm rendered through colonial spatiality and governance, including but not limited to the interrogation, screening, and detention of Operation Anvil, continue in the materiality and the spatial configuration of the communities of Mathare, a materiality and spatiality of neglect and abandonment already configured through urban planning, policing, and demolition -Mathare was bulldozed in 1953, prefiguring the expulsions of the following year (Kimari 2017). Injury and harm, what we might frame as the carceral "afterlives" of empire, are evident in the continuity of criminalization, policing, control, and containment found across Mathare and east Nairobi (Pfingst and Kimari 2021). Unlike the usual arduous weekday commute into the city, Thursday, October 19, 2017, was distinctly different.…”
Section: Collective Bodies Of Movement Protest and Exclusionmentioning
confidence: 99%
“…The injury and harm rendered through colonial spatiality and governance, including but not limited to the interrogation, screening, and detention of Operation Anvil, continue in the materiality and the spatial configuration of the communities of Mathare, a materiality and spatiality of neglect and abandonment already configured through urban planning, policing, and demolition -Mathare was bulldozed in 1953, prefiguring the expulsions of the following year (Kimari 2017). Injury and harm, what we might frame as the carceral "afterlives" of empire, are evident in the continuity of criminalization, policing, control, and containment found across Mathare and east Nairobi (Pfingst and Kimari 2021). Unlike the usual arduous weekday commute into the city, Thursday, October 19, 2017, was distinctly different.…”
Section: Collective Bodies Of Movement Protest and Exclusionmentioning
confidence: 99%
“…We would like to end by outlining some of the important new agendas and directions in this field. First, the articles by Daly, Mester, and Super reflect the increased attention to postcolonial systems of punishment (Alexander, 2013; Berridge, 2016; Bertlesen, 2011; Machava, 2011, 2019; MacDonald 2012; Bruce-Lockhart, 2018; Mbembe, 2019; Quarshie, 2021; Pfingst and Kimari, 2021) but there is still much work to be done in this area. As Bruce-Lockhart (2022) argues, scholars need to critically analyze why and how prisons and other elements of colonial penal systems persisted after independence.…”
Section: Future Directionsmentioning
confidence: 99%
“…To this end, we think there are numerous points where scholars focusing on trends in the United States and Europe could benefit from more closely engaging with African History. For example, those studying electronic monitoring and the close surveillance that attends either bail reform or parole could greatly benefit from studies examining the attempts at close surveillance practiced by colonial and apartheid states (Dlamini, 2020; Pfingst and Kimari, 2021). Similarly, some scholars in the United States have suggested that the racialization of policing and punishment in the United States demonstrates a particularly colonial relationship between the White majority and Black minority, a direction of study that could benefit greatly from the nuanced treatment of race and racial governance that can be found in African Studies (Mamdani, 1996).…”
Section: Future Directionsmentioning
confidence: 99%